PENGUATAN PENGELOLAAN UKM BATIK MALANGAN MELALUI PENINGKATAN KUALITAS DAN KUANTITAS PRODUKSI DAN MANAJEMEN - Lis Lestari S; MAF Suprapti; Lila Khamelda (Jurnal ABM Mengabdi, 2018)
The typical written batik from Malang has enormous potential for development. As a product included in the regional cultural wealth, affordable both nationally and internationally, it is a unique product desired by many domestic and global consumers. The writer has identified the needs of Wiggrade and Wisnu Batik SMEs in Malang for strengthening in the management and development of their business. At the same time, current developments of batik business are in need of rejuvenation and innovation in the production equipment. The problems encountered in the production area are the ineffective and inefficient production process, the low quantity and quality of products, and unsophisticated management, such as lack of capability in preparing bookkeeping records appropriate with the needs of the SMEs. The solution offered to the SMEs is the necessary technological transformation which includes: production aspects capable of efficiently increasing production, increased quantity and quality through the procurement of production tools, trainings to increase the quality and quantity of products, management governance through the preparation of bookkeeping systems appropriate with the needs of the batik SMEs (as the main support of the development of batik business), and training and mentoring in the application of the bookkeeping systems. The results achieved in this activity include the availability of adequate production tools, increase in the quality and quantity of products, availability of bookkeeping systems, and increased understanding in the importance of bookkeeping systems for activity partners.